Case Report: Minocycline-induced drug reaction with eosinophilia and systemic symptoms syndrome: a case report and literature review - Zhao, Zhe; Lu, Ming; Ying, Yingqiu (Frontiers in Pharmacology, 2024)
Minocycline is a tetracycline commonly used for several dermatological diseases. Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rare but severe adverse event which can be caused by minocycline. An 18-year-old male patient developed fever, acute rash, pharyngeal pain, lymphadenopathy, hematologic abnormalities, increased creatinine level, elevated liver enzyme levels, and splenomegaly 4 weeks after the oral treatment of minocycline, 100 mg daily, for acne. Once diagnosed with DRESS syndrome, intravenous methylprednisolone was applied and his clinical manifestations and laboratory results remarkably improved. Then, a total of 13 DRESS syndrome cases induced by minocycline were reviewed and their clinical characteristics were summarized. In these cases, only two patient (15.4%) was present with pharynx involved. In conclusion, we reported a rare minocycline-induced DRESS syndrome who developed fever, eosinophilia, acute rash, pharyngitis, lymphadenopathy, acute kidney injury, hepatitis, and splenomegaly. Our report provides detailed clinical features of minocycline-induced DRESS syndrome, which helps us further understand this severe adverse event.